2021
DOI: 10.1186/s12864-021-07843-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of merged whole blood transcriptomic datasets to identify circulating molecular biomarkers of feed efficiency in growing pigs

Abstract: Background Improving feed efficiency (FE) is an important goal due to its economic and environmental significance for farm animal production. The FE phenotype is complex and based on the measurements of the individual feed consumption and average daily gain during a test period, which is costly and time-consuming. The identification of reliable predictors of FE is a strategy to reduce phenotyping efforts. Results Gene expression data of the whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Fifteen DE-genes were upregulated in the high RFI group of pigs. Rank-based enrichment test for log fold change values showed that expression upregulation in the high RFI group was enriched for immune system associated annotations in agreement with previous studies 14 , 28 . The identified immune system response in colon epithelium might indicate a link between gut immune function, the gut microbiome and FE.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fifteen DE-genes were upregulated in the high RFI group of pigs. Rank-based enrichment test for log fold change values showed that expression upregulation in the high RFI group was enriched for immune system associated annotations in agreement with previous studies 14 , 28 . The identified immune system response in colon epithelium might indicate a link between gut immune function, the gut microbiome and FE.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, metagenomics research has shown an association of dozens of bacterial taxonomic units in gut microbiota with FE 8 , 11 , and metabolomics studies in combination with transcriptomic 9 and GWA studies 10 have revealed significant gene-metabolite pairs. Transcriptomic studies have found FE associated differentially expressed genes (DE-genes) in various tissue, including blood 14 , liver 12 , brain 15 and intestine 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the modest differences in morphology, piglets from the two lines differed in plasma metabolome. In a previous study on the same lines, the use of an NMR metabolomics approach discriminated LRFI and HRFI growing pigs, with the most influential metabolites being AA (phenylalanine, glutamate, and tryptophan) and AA derivates 21 . The present study showed major differences for AA in newborn piglets as well.…”
Section: Discussionmentioning
confidence: 97%
“…However, putative FE genes participated in a wide range of biological processes [ 5 , 6 ] and in many functional pathways in different tissues through gene expression profiles [ 9 ], suggesting that the biological strategies used to improve FE are diverse. Tissue- and organ-specific transcriptomes and miRNA profiles have been widely used to elucidate the molecular basis of inter-individual differences in FE [ 10 , 11 , 12 , 13 ]. In pigs, FE-related transcriptome research has focused on energy homeostasis and energy demand [ 9 , 10 , 14 , 15 , 16 ], mainly in the liver and adipose tissue [ 17 ] and in intestinal, blood, and muscle tissue [ 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue- and organ-specific transcriptomes and miRNA profiles have been widely used to elucidate the molecular basis of inter-individual differences in FE [ 10 , 11 , 12 , 13 ]. In pigs, FE-related transcriptome research has focused on energy homeostasis and energy demand [ 9 , 10 , 14 , 15 , 16 ], mainly in the liver and adipose tissue [ 17 ] and in intestinal, blood, and muscle tissue [ 13 , 18 , 19 ]. The liver is the most important organ involved in metabolism and, as such, plays an important role in converting newly acquired energy into the muscle or adipose tissue, thereby affecting FE [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%